Pemanfaatan Media Sosial Instagram sebagai Sarana Promosi Konser Musik: Studi Deskriptif Kualitatif pada Akun Instagram @Infopensi - Arif Nurhakim; Mayasari Mayasari; Tri Susanto (IAI Nasional Laa Roiba Bogor, 2026)
The development of social media platforms has opened new opportunities in marketing communication, particularly in the creative and entertainment industries. This study aims to describe the application of the Promotion Mix in music concert promotion on the Instagram account @infopensi and to identify the obstacles and supporting factors involved. A descriptive qualitative method with a constructivist paradigm was employed. Data were collected through in-depth interviews, observation, and documentation involving five purposively selected informants, consisting of one account founder and four active followers. Data analysis followed the interactive model of Miles and Huberman. Findings indicate that among the five Promotion Mix elements, advertising and direct and internet marketing are the most dominant. Advertising is implemented through a paid promote mechanism based on a structured rate card encompassing feed posts, Instagram Story, and collab posts. Direct and internet marketing serves as the foundational infrastructure of all promotional activities through the integrated use of Instagram features and a supporting website. Public relations were identified in implicit practices including content verification and partner relationship maintenance. Personal selling appears in limited intensity during initial negotiation stages. Sales promotion, however, lacked sufficient evidence given @infopensi's position as a media service provider rather than a direct ticket seller. The primary obstacle is shifting audience behavior toward TikTok, while supporting factors include 251 thousand followers, a reputation established since 2012, and the diverse use of digital features.